2014
DOI: 10.1149/2.0181409jes
|View full text |Cite
|
Sign up to set email alerts
|

The pH Changes at the Electrode Surface Caused the New Voltammetric Waves in PCET Reactions

Abstract: Proton-coupled electron transfer (PCET) reactions are ubiquitous in chemical and biological processes. However, the role of pH has been a source of confusion, hindering our understanding of the PCET mechanism. In dilute buffered solutions, a new anodic hydroquinone wave depends on the proton acceptor, and two cathodic quinone waves also depend on the pH and the proton donor. New complexes corresponding to the new waves are ruled out because the UV/vis spectra of hydroquinone and quinone did not vary with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…The complex between phosphate and QH 2 could not be detected as the spectrum of QH 2 is independent of phosphate. Therefore, we attribute wave 1 to the drastic decrease in pH at the electrode surface instead of new species . HPO 4 2− is the proton acceptor in phosphate buffer solution.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The complex between phosphate and QH 2 could not be detected as the spectrum of QH 2 is independent of phosphate. Therefore, we attribute wave 1 to the drastic decrease in pH at the electrode surface instead of new species . HPO 4 2− is the proton acceptor in phosphate buffer solution.…”
Section: Resultsmentioning
confidence: 92%
“…We observed that three Q peaks occur in dilute phosphate or phosphite solution (pH=3.35). We concluded that the new waves are generated by acute pH changes near the electrode surface . Therefore, the addition of buffer is necessary for electrochemical research on PCET reactions.…”
Section: Introductionmentioning
confidence: 95%
“…According Figure , the reduction of ferric EDDHA involves the protonation of the phenolic groups, which however is a fast reaction within the time scale of the CV experiments performed . As a result, the solution pH in the diffusion layer of the electrode increases during the cathodic scan of a CV experiment …”
Section: Resultsmentioning
confidence: 99%
“…4 are attributed to the sharp pH change at the electrode surface. 33,34 Thus, the buffer capacity will affect the cyclization reaction of catecholamines.…”
Section: H758mentioning
confidence: 99%
“…We have investigated the electrochemical behavior of hydroquinone and p-benzoquinone in the dilute buffer solution. 34 We revealed that the sharp pH change at the electrode surface caused the new voltammetric waves in proton-coupled electron transfer (PCET) reactions. According to our previous study, the pH at the electrode surface regulates the electrochemical behavior of the PCET reactions, not the pH of the bulk solution.…”
Section: H758mentioning
confidence: 99%